Hair dye dermatitis and p-phenylenediamine contact sensitivity: A preliminary report - Mrinal Gupta; Vikram K Mahajan; Karaninder S Mehta; Pushpinder S Chauhan (Wolters Kluwer Medknow Publications, 2015)
Background: The contact allergic reactions from p-phenylenediamine (PPD) in hair dyes vary from mild contact dermatitis to severe life- threatening events (angioedema, bronchospasm, asthma, renal impairment). Objectives: To study the clinical patterns and PPD contact sensitivity in patients with hair-dye dermatitis. Materials and Methods: Eighty (M: F 47:33) consecutive patients aged between 18 and 74 years suspected to have contact allergy from hair dye were studied by patch testing with Indian Standard Series including p-phenylenediamine (PPD, 1.0% pet). Results: 54 Fifty-four (M: F 21:33) patients showed positive patch tests from PPD. Eight of these patients also showed positive patch test reaction from fragrance mix, thiuram mix, paraben mix, or colophony. Fifty-seven (71%) patients affected were aged older than 40 years. The duration of dermatitis varied from < 1 month to > 1 year with exacerbation following hair coloring. Forty-nine patients had dermatitis of scalp and/or scalp margins and 23 patients had face and neck dermatitis. Periorbital dermatitis, chronic actinic dermatitis, and erythema multiforme-like lesions were seen in 4, 2, and 1 patients, respectively. Conclusions: Hair dyes and PPD constitute a significant cause of contact dermatitis. There is an urgent need for creating consumer awareness regarding hair-dyes contact sensitivity and the significance of performing sensitivity testing prior to actual use.